Impact fragmentation of metal nanoparticle agglomerates - Peukert, Wolfgang; Seipenbusch, Martin; Toneva, Petya Ivanova; Weber, Alfred P. (Particle & Particle Systems Characterization, 2007)
Deagglomeration experiments were performed with agglomerates of nanoparticles of Ni and Pt. The fragmentation was induced by high velocity impaction of the agglomerates in a single-stage low pressure impactor and the fragmentation patterns were evaluated by TEM analysis. Weibull statistics are employed for a quantitative description of the fragmentation behavior. This study shows that for well-defined interparticle contacts, the impact fragmentation technique combined with the evaluation according to Weibull statistics, allows the recovery of the expected size dependencies. For Pt and Ag, the adhesion force particle size dependency was dominated by van der Waals forces. In contrast, the adhesion force between Ni particles in the size range from 12-28 nm revealed a much stronger increase with particle size. This phenomenon may be attributed to permanent magnetic dipole moments which are also reflected in the chain-like shape of the agglomerates. For nanoparticle agglomerates with less well-defined contacts, such as those in industrial environments, the method provides a promising application to reveal the bond strength and cohesiveness of nanoparticle powders. © 2007 WILEY-VCH Verlag GmbH & Co. KGaA.
Keywords: Deagglomeration; Diffusional agglomeration; Nanoparticle agglomerates; Weibull statistics